Associations between violence, criminality, and cognitive control deficits among young men living in low resource communities in South Africa. Issue 1 (14th October 2019) - Bantjes, Jason; Rabie, Stephan; Almirol, Ellen; Gordon, Sarah; Stewart, Jackie; Goldbeck, Cameron; Weiss, Robert; Tomlinson, Mark; Rotheram‐Borus, Mary Jane
Abstract: Despite empirical support for "Self‐control theory" in criminology, there is controversy about how self‐control should be operationalized. Working within the framework of "self‐control theory, " we investigated if violence and criminal behaviors are associated with nine distinct dimensions of cognitive control in a community sample of young men ( n = 654) living in peri‐urban townships in South Africa. Cognitive control was assessed using the Behavior Rating Inventory of Executive Function. Multivariate statistical analysis was used, to identify associations between violence and criminality, and deaggregated measures of nine distinct components of cognitive control. Fifteen percent of the sample reported recent violence, 27% had been in physical fights with family/friends in the preceding 6 months, 10% reported being arrested, 4% reported forced sexual contact, and 26% reported intimate partner violence (IPV). Controlling for substance use and sociodemographic variables, contact with the criminal justice system and violence were associated with deficits in all domains of cognitive control. Forced sexual contact was associated with behavioral dysregulation. IPV was associated with behavior dysregulation and executive control dysfunction. Future studies might utilize deaggregated measures of self‐control to provide further insight into links between particular components of cognitive control and various forms of offending and violence.